2018
DOI: 10.1108/dat-08-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

When two worlds collide: critical reflection on co-production

Abstract: Purpose The purpose of this paper is to report the findings from reflexive data collection on the evolving co-production research relationship between the two “worlds” of community and academia: people with lived experience and their community intermediaries and academic researchers. It reports analysis of reflections on experience as the different partners explore and evaluate their own experiences of co-productive research within the context of substance use recovery co-production research. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 14 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…The third article presented three case studies from Australia highlighting learnings in research with highly marginalized young people Reflective articles: Three articles including a reflective article on developing and sustaining an emancipatory research project between Irish, Ugandan, Tanzanian and South African partners; a UK reflective article on co‐producing research with an intermediary community partner; a reflective article identifying methods to engage hard to reach patients in patient‐centred outcomes Grey literature: Three grey literature articles/reports, including an Irish‐based report on what was learned from an emancipatory research partnership involving community and university partners to capture the experiences of Travellers and people with experience of the asylum process in respect to access of public services .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The third article presented three case studies from Australia highlighting learnings in research with highly marginalized young people Reflective articles: Three articles including a reflective article on developing and sustaining an emancipatory research project between Irish, Ugandan, Tanzanian and South African partners; a UK reflective article on co‐producing research with an intermediary community partner; a reflective article identifying methods to engage hard to reach patients in patient‐centred outcomes Grey literature: Three grey literature articles/reports, including an Irish‐based report on what was learned from an emancipatory research partnership involving community and university partners to capture the experiences of Travellers and people with experience of the asylum process in respect to access of public services .…”
Section: Resultsmentioning
confidence: 99%
“…The review found that engagement with seldom heard groups needs to occur in safe, accessible and inclusive spaces . Ensuring spaces are accessible needs to be guaranteed by undertaking an audit at the start of the research, which should be monitored and reviewed throughout the project .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations